Glutaredoxin2 reduces age-associated B cell differentiation through maintaining redox homeostasis - Jiang, Yuan; Sun, Chunli; He, Qilin; Liu, Shujun; Tian, Shihao; Zhang, Yan; Du, Yatao; Li, Fubin; Zhang, Huihui (Frontiers in Pharmacology, 2025)
BackgroundThe redox system plays a pivotal role in autoimmune diseases and cancer, with oxidative stress and antioxidant adaptations driving pathological processes. Age/autoimmunity-associated B cells (ABCs), characterized by elevated ROS levels, are implicated in autoimmune disorders such as systemic lupus erythematosus (SLE). However, the mechanisms linking ROS to ABC differentiation remain unclear. Glutaredoxin 2 (Grx2), a key oxidoreductase, regulates redox homeostasis, but its role in autoimmune B cell biology is underexplored.MethodsUsing wild-type and Grx2-knockout mice, we examined ROS levels and ABC differentiation. In vitro, ABC differentiation was induced with IL-21 and TLR7 agonist, and the effect of the antioxidant N-Acetyl-L-Cysteine (NAC) was assessed. The SLE-prone ShipΔB model crossed with Grx2−/− mice was used to evaluate autoimmune pathology.ResultsABCs exhibited higher ROS levels than follicular B cells, and NAC reduced ABC differentiation rate by 50%, demonstrating ROS dependency. Grx2 deficiency amplified ROS levels and ABC proportions in aged mice, correlating with accelerated autoimmunity. In ShipΔB mice, Grx2 deletion exacerbated ABC differentiation, CD4+ T cell activation, and anti-dsDNA autoantibody titers.ConclusionsGrx2 acts as a redox checkpoint that limits ABC-driven autoimmunity by modulating ROS. The Grx2–ROS axis represents a potential therapeutic target for SLE and related chronic inflammatory diseases.